How do they train teachers in Secondary Education in Germany? - Chaves Salas, Ana Lupita (2017)
This bibliographical research shows the model of teacher education for secondary education in Germany, especially at Osnabrück University located in the region of Lower Saxony. This information has been obtained as a product of investigation in the project: Models of Teacher Education in Secondary Education: analysis and proposal, registered at the Institute of Education at the Faculty of Education of the University of Costa Rica, analyzing the curricula for teacher training in different countries, among them the one which is represented in this article. Moreover the article describes the form and levels of the German education system including dual vocational education. Highlighted is the importance of the definition of standards for the formation of teachers that takes place in that country, at the federal level, that contributes to establish a basic professional profile of the teacher, which should be taken care of by the universities that form these professionals, as well as the relevance of the concurrent training model, among other subjects. As a conclusion some aspects of teacher training in Germany are highlighted that could serve as reference to improve the teacher training in Universities in our country.